Composition of biopesticides for crop protection – current state and prospects (review) - A. I. Homyak; A. M. Asaturova (Юг России: экология, развитие, 2024)
Aim. To summarise and analyse available information on research into biopesticide compositions aimed at enhancing their effectiveness and to assess prospects for the development of this field so as to determine the influence of components on the effectiveness of biopesticides for agricultural crop protection.This review article presents the results of studies of components included in the compositions of microorganism‐based biopesticides based on a system analysis. It is noted that the selection of biopesticide components must be carried out in accordance with the requirements for products recommended for use in ecological and organic farming systems. It is indicated that the choice of optimal formulation is associated with the characteristics of the producer strains, their trophic needs and resistance to biotic and abiotic factors and with the characteristics of the biopesticide application technology (seed treatment, application to the soil or treatment of plants during vegetation), as well as the type of equipment used.Knowledge of the basic requirements for biopesticide formulations will help maintain the viability and biological activity of microbial agents during storage of biopesticides, taking into account the sensitivity of producer strains to environmental conditions. Selection of optimal carriers, adhesives, stabilisers, thickeners and synergists, taking into account the technology of application of the biopesticide and the target pathogen, will facilitate the development and appearance on the market of new biopesticides for protecting agricultural crops from diseases.